FIGURATIVE LANGUAGES FOUND IN FROZEN MOVIE SELECTED SONGS - Ni Putu Selly Kusmirayanti; Ida Bagus Gde Nova Winarta; Ni Wayan Suastini (University of Darussalam Gontor, 2021)
This study entitled “Figurative Languages Found in Frozen Movie Selected Song”. In general, figurative language is a type of language that departs from the language used traditionally and literally. This study aims to spot and describe the inner meaning of figurative language found within the Frozen Movie Original soundtrack. This research uses a descriptive qualitative method to describe the types found and the meanings contained in the lyrics of the song Frozen. This article uses theory from Perrine (1969) to explain the types of figurative language, and theory from Leech (1981) which describes the meaning contained in song lyrics. From the research conducted, 11 data were used, and of the 11 types found, 4 types contained in the song lyrics can be identified, including Personification with 3 data, Apostrophe with 3 data, Overstatement with 3 data, and simile with 2 data. This article aims to provide lessons to the public in order to analyze the lyrics of the songs we listen to so that we understand what the songs mean.